Sikap Peserta Didik Terhadap Sains di Sekolah Menengah Pertama dan Madrasah Tsanawiyah Negeri Kabupaten Aceh Jaya - Evendi Evendi; Ismul Huda; Yusrizal Yusrizal; A. Halim; Saminan Saminan; Manna Wassalwa (Jurnal Penelitian Pendidikan IPA, 2022)
Attitudes towards science are attitudes that appear in students before and after learning science. The higher the attitude of students towards science subjects, the higher their learning outcomes will be. On the other hand, the lower the students' attitudes towards science subjects, the lower their learning outcomes will be. This study aims to analyze how students' attitudes towards science. This research method is survey research using the Test of Science Related Attitude (TOSRA) instrument with a 5-point Likert scale on 161 students as the research sample. Data analysis was done by statistical descriptive. The results of the study on five indicators of students' attitudes towards science obtained the highest response, namely the pleasure of learning science was in the agreed criteria (39.40%) and was in the positive category (47.2%); Interest in spending time studying science is in the agreed criteria (37.29%) and is in the positive attitude category (54.7%); Interest in a career in science is found in the agreed criteria (34.43%) and in the positive attitude category (50.3%); The attitude of scientific investigation was obtained with the criteria of agreeing (29.71%) and was in the category of positive attitude (77%); and the social implications of science are obtained on the agreed criteria (37.04%) and are in the positive attitude category (72%). Overall, students' attitudes towards science with the highest responses were found in the agreed criteria (35.56%) with the category of positive attitudes (75.8%) in SMP and MTsN Aceh Jaya District